Biochemical insights into cadmium detoxification mechanism of Coccomyxa sp. IITRSTKM4. Issue 4 (August 2022) - Tripathi, Shweta; Behera, Tapasranjan; Poluri, Krishna Mohan
Abstract: The unabated release of heavy metals like Cd in aquatic bodies has created a challenging situation in front of humankind. The existing physico-chemical Cd removal techniques such as precipitation, ion exchange, membrane filtration etc., further generate more concentrated Cd-laden discards. As a sustainable alternative, employing green technologies such as microalgae-based remediation offers an economic and eco-friendly approach to remove Cd. In this context, the present investigation illustrates the Cd removal efficiency of viable Coccomyxa sp. IITRSTKM4 cells and its survival mechanism to tolerate Cd stress. The removal optimization experiments were performed using Box-Behnken design. The microalga tolerated Cd stress with IC50 value of 18.5 ppm and removed ~ 88% of Cd when exposed to 15 ppm Cd. Apart from adsorption on cell wall and chelation by EPS, Cd uptake through Ca channels mediated its accumulation inside the cells. To tolerate the Cd stress, Coccomyxa sp. triggered the accumulation of lipids, carbohydrates, and a convoy of non-enzymatic and enzymatic molecules to rewire its redox system. Further, fatty acid methyl ester (FAME) analysis highlighted the substantial rise in saturated/monounsaturated fatty acids, which improved the iodine value and oxidative stability of the derived biodiesel. Altogether, the outcomes of the study dissected the resilient nature of Coccomyxa sp. IITRSTKM4 to survive Cd toxicity suggesting a sustainable and economical solution integrating the efficient Cd removal and biofuel production. Graphical Abstract: ga1 Highlights: Response surface methodology was deployed to optimize Cd removal. Coccomyxa sp. IITRSTKM4 removed ~ 89% Cd from the media. Coordinated action of thiols with antioxidant enzymes regulated the redox system. The microalga remodeled the carbon pools towards energy compounds in Cd stress.